A Comprehensive Study on the Effect of Dimethyl Carbonate Oxygenate and EGR on Emission Reduction, Combustion Analysis, and Performance Enhancement of a CRDI Diesel Engine Using a Blend of Diesel and Prosopis juliflora Biodiesel. (14th May 2022) - Ramesh, T.; Sathiyagnanam, A.P.; Poures, Melvin Victor De; Murugan, P.
Abstract : This paper examines the combined effects of ignition improvers (DMC) and EGR on the CRDI small single-cylinder diesel engine's performance, combustion, and emissions. In this experimentation, 20% (B20) optimal mix of Prosopis juliflora oil biodiesel (PJOB) and 5 ml dimethyl carbonate (DMC) additive was used as test fuel. The fuel handling CRDI system factors such as injection pressure set at 600 bar and injection timing set to 21 (bTDC) with a compression ratio of 16 were considered for the study. For the EGR trial, 20% of the exhaust gas was recirculated under various BMEP circumstances. The test was performed with and without EGR and DMC additive conditions like (i) diesel @ 0% EGR, (ii) diesel + 5 ml DMC @ 20% EGR, (iii) B20 @ 0% EGR, and (iv) B20 + 5 ml DMC @ 20% EGR at the engine power output. The amalgamation of dimethyl carbonate (DMC) additives and EGR reduces NOx and smoke while increasing CO and HC emissions. In addition, the DMC additive and EGR improve thermal efficiency slightly. The overall clubbing of DMC additive and EGR rate indicates better performance for the selected factors than a CRDI engine with a six-hole conventional mechanical fuel injection system. The outcome of the work clearly demonstrates that both the 5 ml DMC additive and the 20% EGR rate of the B20 blend show optimum values of BTE, BSFC, and EGT of 32.93%, 0.27 kg/kw·hr, and 310.89°C, which is closer to diesel. Factors of combustion like cylinder peak pressure (CPP) and heat release rate (HRR) are 70.93 bar and 58.13 J/deg. The tailpipe exhaust of NOx and smoke is 1681 ppm and 31.30 (% vol), which is less than diesel. The HC and CO levels are 93 ppm and 0.38 (% vol), respectively, which are significantly higher than diesel fuel.